(untitled) (International Journal of Engineering and Computer Science, 2018)
Software is exploited in most of the fields today and plays an important role in both economic and social development. Mature software industries rely on early software cost estimation. Accuracy in estimations allows the company to develop appropriate time plan and estimate the most feasible budget for the project. A major cause of failure of many software projects is the lack of accurate and early cost estimation. However, irrespective of great deal of importance, estimating the time and development cost accurately is still a challenge in software industry. Barry Boehm proposed Constructive Cost Model also known as, COCOMO Model which used basic regression formula with parameters derived from historical project data and characteristics of the current project for estimating the cost of software. This model is a high risk due to low accuracy and lack of reliability. This is where the need of optimization comes in. Various approaches like Genetic Algorithm have already been applied for tuning of the parameters of COCOMO in order to increase its accuracy and reliability. Regardless, that humans are the most intelligent social animals, an approach based on crowd dynamics, opinion dynamics, language dynamics is seldom used for optimization. Interaction between humans gives rise to different kind of opinions in a society. The process of opinion formation evolves from collective intelligence emerging from integrative forces of social influence with disintegrative effects of individualization. Opinion dynamics leads to efficient decision making and so, we propose an approach based on human opinion dynamics for effective and accurate software cost estimation.